Biodegradation of enrofloxacin by microbial consortia obtained from rhizosediments of two estuarine plants. (1st February 2019) - Santos, Filipa; Mucha, Ana P.; Alexandrino, Diogo A.M.; Almeida, C. Marisa R.; Carvalho, Maria F.
Abstract: This study aimed to investigate the potential of microbial communities from the rhizosediment of two plants - Phragmites australis and Juncus maritimus - occurring in an estuarine area subjected to a high anthropogenic impact, to biodegrade ENR, a commonly used veterinary antibiotic. An enrichment process with 1 mgL −1 of ENR was conducted during ca. 9 months, using acetate as a co-substrate. After this, the enriched microbial consortia were challenged with higher ENR concentrations of 2 and 3 mgL −1 . Microbial cultures enriched with 1 mgL −1 of ENR were capable of biodegrading this antibiotic, though not completely. By the end of the enrichment phase, microbial cultures were defluorinating an average of 50% of the ENR supplemented. Higher ENR concentrations led to lower biodegradation performances, suggesting a possible toxic/inhibitory effect in the microbial cultures. Phylogenetic identification of the microorganisms isolated from microbial cultures enriched with ENR revealed a high taxonomical diversity, with microorganisms belonging mainly to Proteobacteria and Bacteroidetes phyla. Assemblage of the obtained isolated strains (according to the enriched cultures from which they were isolated) revealed that the resulting consortia were also capable of degrading ENR, indicating that the main microbial players in the biodegradation of this antibiotic were isolated. These consortia also showed to be more robust to degrade higher concentrations of ENR than the corresponding enriched cultures. This study shows that microorganisms derived from rhizosediments of the selected plants, exhibit capacity to biodegrade ENR, though not completely for the concentrations tested, and may be further explored for the development of bioremediation strategies for the treatment of this antibiotic. Highlights: Capacity of microbes from rhizosediment of estuary plants to degrade ENR was assessed. Enriched microbial cultures were able to degrade ENR though not completely. Exposure to higher ENR concentrations led to lower biodegradation performances. Degrading strains predominantly belonged to Proteobacteria and Bacteroidetes phyla. Assemblage of isolates from enriched cultures also resulted in ENR biodegradation.